Counseling in psoriasis: overcoming the concerns and challenges - Godse, Kiran; Parasramani, S. G.; De, Abhishek; Singh, Nitesh Kumar; Kawatra, Pallavi (International Journal of Research in Dermatology, 2021)
Psoriasis is a systemic, immune-mediated disorder, characterized by systemic inflammation predominantly in skin and joints with significant physical and psychosocial consequences. It is a chronic disease with an unpredictable journey consisting of flares and remissions. Psoriasis has also been linked to loss of self-esteem in patients, depression and suicidal tendencies. In addition, it also contributes to financial burden due to the long-term management. This results in negative impact on the caregivers and family of the patient. Due to these multiple factors, there has been low compliance to therapy and higher likelihood of discontinuation of treatment. Considering the emotional aspect involved in this disease, counseling of the patients becomes one of the integral pillars for the management of the disease. Hence, the clinician’s role becomes significant, due to limited access to counselors, therapists and social groups, in our country. The present reviewdescribes the impact of psoriasis on the patient’s life and the practical approaches that may be taken to counsel the patient of psoriasis.